INFLUÊNCIA DO GANHO DE PESO MATERNO NO ESTADO NUTRICIONAL DO RECÉM-NASCIDO (Revista Contexto & Saúde, 2020)
This study aims to analyze the influence of maternal weight gain on the newborn’s nutritional status. This is a quantitative study with a cross-sectional design. The sample consisted of mothers and babies born in a public hospital in Santa Maria - RS. In the first 48 hours after delivery, data were collected from medical records, the pregnant woman’s card and interviews with the puerperal woman. Data collection consisted of a questionnaire, in which they were divided into blocks: pregnancy, mother and child. 184 mothers and newborns were evaluated, the mean pre-gestational weight was 60,96±11,57 kg, and the mean gestational weight gain was 13±5,18 kg, regarding the weight classification for gestational age, 145 (81%) of the newborns were found to be adequate for gestational age, 16 (8,9%) big for gestational age and 18 (10,1%) great for gestational age. It is noteworthy that the newborns with adequate weight for gestational age were the ones who obtained a statistically higher score for socioeconomic and health items. After analyzing the influence of maternal weight gain on nutritional status, it was observed that the number of prenatal consultations, adequate gestational weight gain, education and family income, associated, interfered in some way in the nutritional status of the mothers and newborns.